Uvod v računalniško dinamiko tekočin - Hriberšek, Matjaž (University of Maribor Press, 2017)
Introduction to Computational Fluid Dynamics. Traditional design methods are increasingly replaced by the use of computer based simulation techniques. In order for an engineer to exploit simulation tools capabilities, one has to understand the physical background of a problem, but also have to have a good knowledge in numerical methods. The collected topics from Computational Fluid Dynamics (CFD) deal with the area of fluid dynamics. The first part of the text is devoted to explanation of the numerical methods, used in transformation of partial differential equations of the fluid flow into their algebraic equivalent, forming the basis of any CFD algorithm. The second part deals with modeling of boundary conditions and turbulence, the most important parts of a CFD code. The text serves as a complement to the lectures in the subject of CFD at the master of science study in Mechanical Engineering, but is also recommended to students of other engineering study programmes.